Find the product of:
(i) 2x, 5y and 7z                 (ii) 4xy, 5x2y2 and 6x3y3
Simplify the expressions and evaluate them as directed:
(i) x(x – 3) + 2 for x = 1 (ii) 3y(2y – 7) – 3(y – 4) – 63 for y = –2.
Multiply the binomials
(2x + 5) and (4x - 3)
(2x + 5) x (4x - 3) = 2x(4x - 3) + 5(4x - 3)
                         = (2x x 4x) - (2x X 3) + ( 5 X 4x) - ( 5 x 3)
                         = 8x2 - 6x + 20x - 15
                         = 8x2 - 6x + 20x - 15
                         = 8x2 + (- 6x + 20)x - 15
                         = 8x2 +14x - 15